p75 Is Required for the Establishment of Postnatal Sensory Neuron Diversity by Potentiating Ret Signaling - Zhijiang Chen; Christopher R. Donnelly; Bertha Dominguez; Yoshinobu Harada; Weichun Lin; Alan S. Halim; Tasha G. Bengoechea; Brian A. Pierchala; Kuo-Fen Lee (Cell Reports, 2017)
Producing the neuronal diversity required to adequately discriminate all elements of somatosensation is a complex task during organogenesis. The mechanisms guiding this process during dorsal root ganglion (DRG) sensory neuron specification remain poorly understood. Here, we show that the p75 neurotrophin receptor interacts with Ret and its GFRα co-receptor upon stimulation with glial cell line-derived neurotrophic factor (GDNF). Furthermore, we demonstrate that p75 is required for GDNF-mediated Ret activation, survival, and cell surface localization of Ret in DRG neurons. In mice in which p75 is deleted specifically within sensory neurons beginning at E12.5, we observe that approximately 20% of neurons are lost between P14 and adulthood, and these losses selectively occur within a subpopulation of Ret+ nonpeptidergic nociceptors, with neurons expressing low levels of Ret impacted most heavily. These results suggest that p75 is required for the development of the nonpeptidergic nociceptor lineage by fine-tuning Ret-mediated trophic support.